KONFLIK KEWENANGAN DALAM PEMAKZULAN KEPALA DAERAH/WAKIL KEPALA DAERAH - La Ode Muhaimin (Mimbar Hukum, 2022)
Abstract Clustering of authority to impeach the regional head or vice regional head builds a conflict of authority between DPRD and the president/Minister of Home Affairs regarding the regional head or vice regional head carrying out crime that causes a widespread crisis of public trust by the intersection between the two clusters. This research type is normative law and uses legal approach conceptually and presented qualitatively. Conflict of authority can be revealed when the report of a crime against the regional head or vice regional head is simultaneously carried out to DPRD and the police.. Assuming that DPRD and the police appear in the phase of impeachment, there will be clashes between clusters of authority. This is due to the authority in the Presidential/Minister of Home Affairs cluster and the authority in the DPRD cluster to provide responses. Finally , the DPRD’s political process and the police's legal process could be shown. The conflict of authority increases as the results of the investigation between the DPRD and the police differ. For instance, in the case of blasphemy committed by Basuki Cahaya Purnama. The reconceptualization of DPRD rights will eliminate potential conflicts of authority to impeach regional heads or vice regional heads that carry out criminal acts and build a crisis of public trust. Abstrak Klasterisasi kewenangan pemakzulan kepala daerah/wakil kepala daerah menimbulkan konflik kewenangan antara DPRD dan Presiden/Menteri Dalam Negeri dalam hal kepala daerah/wakil kepala daerah melakukan tindak pidana yang memicu krisis kepercayaan publik yang meluas karena adanya persinggungan antar dua klaster. Jenis penelitian hukum normatif, menggunakan pendekatan undang-undang dan konseptual serta disajikan secara kualitatif. Konflik kewenangan muncul tatkala laporan tindak pidana terhadap kepala daerah/wakil kepala daerah bersamaan ke DPRD dan kepolisian. Apabila DPRD memulai tahapan pemakzulan dan kepolisian juga memulai proses hukum maka benturan antar klaster kewenangan potensial terjadi.. Konflik kewenangan bertambah bilamana hasil penyelidikan DPRD dan kepolisian berbeda. Misalnya, dalam kasus penodaan agama yang dilakukan oleh Basuki Cahaya Purnama. Masing-masing memiliki kewenangan yang diatur dalam klaster kewenangan masing-masing pula untuk menanggapinya.Akhirnya proses politik di DPRD dan proses hukum di kepolisian dapat tersaji. Rekonseptualisasi hak DPRD akan menghilangkan potensi konflik kewenangan dalam hal pemakzulan kepala daerah/wakil kepala daerah yang melakukan tindak pidana yang menimbulkan krisis kepercayaan masyarakat.